HUBUNGAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG FILARIASIS DENGAN PENCEGAHAN PENYAKIT FILARIASIS DI RW 05 KELURAHAN BEJI TIMUR KOTA DEPOK - Inayati, Umi Bariyah; Herlina, Santi (Jurnal Keperawatan Widya Gantari Indonesia, 2014)
The elephantiasis (filariasis) disease is a contagious chronically disease, which caused by filaria worm infection. The disease emerge symptom such as periodic fever, lymph gland chafe, edema.In the Depok city is included endemic area of filariasis. In Depok city, microfilaria rate is >1 % in October 2008. The purpose of this research is to identitify knowledge filariasis with the prevention filariasis desease. The method of this research is to use quantitative description and cross sectional approach. The method of collecting the data conducted by questionnaire and doing interview. Population were taken from the whole of society in the Rw 05 kelurahan Beji east Depok city with the taken sample 255 people. The research variable consists of independent variable and dependent variable. Independent variable at this research is knowledge filariasis and dependent variable on this research is prevention program of filariasis desease. From the research about the relationship of knowledge filariasis with the prevention filariasis desease there were relationship, existence of relation having a meaning of between knowledge with prevention program of filariasis desease in the Rw 05 kelurahan Beji east Depok city.  Suggest to the heath officer to improve their behavior by giving continues counseling, give optimum health service to the society, so that the people become sure on the given health service, and also to give interest and motivation for other researchers to improve the research output by doing deeper research in other place